2003
DOI: 10.1017/s0952523803202108
|View full text |Cite
|
Sign up to set email alerts
|

Structure–function analysis of rods and cones in juvenile, adult, and aged C57BL/6 and Balb/c mice

Abstract: To determine whether the photoreceptors change structurally and functionally during aging, and to analyze whether pigmentation in the retinal pigment epithelium might be a contributing factor. Young, adult, and aged C57BL/6 and Balb/c mice (1, 4, and 17 months of age) were housed under a 12-h light/12-h dark cycle, with an ambient light intensity at the eye level of the mice of 85 +/- 18 lux. Scotopic single-flash and photopic-flicker electroretinograms (ERGs) after complete dark adaptation were used to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
106
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(140 citation statements)
references
References 30 publications
34
106
0
Order By: Relevance
“…5B). The ERG responses of normal animals under both scotopic and photopic conditions were similar to those reported previously for aged pigmented mice (18). These data indicate that rod photoreceptor function is compromised in the cfh Ϫ/Ϫ mice, as shown by the reduction in amplitude and change in slope of the a-wave of the ERG.…”
Section: Cfh Deficiency Results In Rod Photoreceptorsupporting
confidence: 73%
“…5B). The ERG responses of normal animals under both scotopic and photopic conditions were similar to those reported previously for aged pigmented mice (18). These data indicate that rod photoreceptor function is compromised in the cfh Ϫ/Ϫ mice, as shown by the reduction in amplitude and change in slope of the a-wave of the ERG.…”
Section: Cfh Deficiency Results In Rod Photoreceptorsupporting
confidence: 73%
“…1 B and C). These results suggest that the functional deficit seen in the young adult CA XIV-null mice is not progressive, but that the background strain has an age-related decline that is seen in both the wild-type and mutant mice (13).…”
Section: Erg Responsesmentioning
confidence: 66%
“…Effects on Control APB mice were much smaller. In previous studies by other investigators, the amplitudes of dark-adapted a-waves and b-wave were found to be reduced as mice aged for both C57BL/6 mice (pigmented mice) and Balb/c mice (albino mice) (Gresh et al, 2003;Li et al, 2001). Between four and 17 months of age, there was a substantial loss of rod photoreceptors (more in the albino mice), which contributed to the reduced ERG amplitudes.…”
Section: Effects Of Aging On the Light-adapted Erg Of Mice Lacking B-mentioning
confidence: 76%
“…Between four and 17 months of age, there was a substantial loss of rod photoreceptors (more in the albino mice), which contributed to the reduced ERG amplitudes. But aging effects have been less obvious for cones, whose counts (middle wavelength) were reduced in aged Balb/c mice, but not in C57BL/6 mice (Gresh et al, 2003;Jacobs and Williams, 2007;Li et al, 2001). Cone-driven flash ERGs were found to be reduced in mice that are a year old, and light-adapted flicker ERG amplitudes were affected, but only mildly in the pigmented mice (Jacobs et al, 2007;Li et al, 2001).…”
Section: Effects Of Aging On the Light-adapted Erg Of Mice Lacking B-mentioning
confidence: 99%